Photoheterotrophic Hydrogen Production of Rhodobacter sphaeroides KCTC 1434 under alternating Ar and N2 Headspace Gas - Ventura, Ruby Lynn G. (Philippine Journal of Science, 2019)
In this paper, the effect of switching argon (Ar) and nitrogen (N2) headspace gases during the onset of photofermentative H2 production on butyrate and propionate was studied using Rhodobacter sphaeroides KCTC 1434. Reactor headspace were initially purged with N2 in the first set-up, while Ar was used in the second set-up. After 60 h, the first set of reactors were repurged with N2 (PN2R, BN2R); while the second set were replaced with Ar (PArR, BArR). Results showed that replacement with N2 automatically decreased H2 productivity in propionate and butyrate by 5.5 and 4.0 times, respectively. Replacement with N2 led to changes in cell densities and increased final pH in the culture medium. On the other hand, initial exposure to N2 and subsequent re-purging with Ar significantly increased (p = 7.87 x 10–10) cell weight and delayed entry of the strain to stationary phase of cell growth. H2 production lag times were determined to be 144 h for PArR (Substrate conversion efficiency, SCE = 96.63%) and 172 h for BArR (SCE = 55.60%). Exposure to any of the gases did not bring significant difference in substrate consumption. Overall, the investigation showed that utilizing N2-to-Ar headspace purging is feasible in photofermentation setup. Further exploration involving pH control and quantification of ammonia (NH3) and polyhydroxybutyrate (PHB) may be carried to extend the use of this setup in a photofermentation system.